Clinical approach of Aavarana Vata W.S.R to Gastro intestinal tract - P.Sushma; M.Srivani (International Journal of Pharmacy and Analytical Research, 2022)
Avarana is a very interesting mechanism of pathogenesis explained in ayurvedic treatises. It is also one of the least understood concepts among the basic mechanisms of ayurvedic fundamentals. It is as unique as well .Now a days, most of diseases come under samsargaja and aavarana janya according to modern era diet and regimen. We use the term aavarana to vata mostly as other doshas are pangu and there movement depend on movement of vata. Different clinical conditions present like aavarana , depending on the stage of disease. Treatment of aavarana is easy,if provided diagnosis is impeccable. This paper aims at narrating the various aspects of aavarna w.s.r. to git & to discuss them on light of clinical manifestation.